The Effectiveness of a Program Using Modeling Learning Strategy in Developing Self-Esteem in Early Childhood - Al-Assaf, Kady Mohammed Abdullah (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed at detecting the effectiveness of a program based on modeling learning strategy in enabling children with self-esteem skills (self-entitlement, self-confidence, self-protection) in early childhood. The researcher used the quasi-experimental method with two-group due to its suitability to the nature of the current research, where the sample is divided into two groups, one of them is the experimental group and the other is the control group. The researcher prepared and used the following tools: the illustrated self-esteem scale (prepared by the researcher), and the program based on the modeling learning strategy in raising the level of self-esteem for children in early childhood (prepared by the researcher), It was applied to a sample of (60) children from early childhood, with an average age of (6-7) years. The results of the current research revealed the effectiveness of a program using the modeling learning strategy in developing self-esteem in early childhood, as was evident from the post-measurement of the experimental group compared to the control group, in addition to the continuity of the positive effect in the experimental group, as was evident from the follow-up measurement of the children of the study sample and was shown by the results of its hypotheses.